2012
DOI: 10.2118/146944-pa
|View full text |Cite
|
Sign up to set email alerts
|

Gas Permeability of Shale

Abstract: Permeability is one of the most fundamental properties of any reservoir rock required for modeling hydrocarbon production. However, shale permeability has not yet been understood fully because of the complexities involved in modeling flow through nanoscale throats. In this paper, we analyze the effects of adsorbed layers of methane (CH 4 ) and of gas slippage at pore walls on the flow behavior in individual conduits of simple geometry and in networks of such conduits. The network is based on scanning elecron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(83 citation statements)
references
References 14 publications
2
76
0
Order By: Relevance
“…The pulse-decay permeability measurement method has been widely recognized as a way to identify the ultra-low permeability rocks [28,30,[48][49][50][51][52][53]. Because the conventional permeability measurement is based on recording the flow rate during the experiment, the flow rate through the ultra-low permeability rock is too small to be measured exactly under the precision of present equipment.…”
Section: Permeability Stress Sensitivitymentioning
confidence: 99%
“…The pulse-decay permeability measurement method has been widely recognized as a way to identify the ultra-low permeability rocks [28,30,[48][49][50][51][52][53]. Because the conventional permeability measurement is based on recording the flow rate during the experiment, the flow rate through the ultra-low permeability rock is too small to be measured exactly under the precision of present equipment.…”
Section: Permeability Stress Sensitivitymentioning
confidence: 99%
“…In order to analyze production dynamics in shale gas reservoirs, an extended dynamic-slippage model was put forward by Clarkson et al [19,20]. Civan et al [21], Sakhaee and Bryant [22] extended Knudsen diffusion into slippage factor to describe gas transport in shales. Anderson et al [23] proposed a model to describe the transport mechanisms, which is related to the experiment empirical coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…In order to propose corrections for Non-Darcy flow over different flow regions in nanopore space, numerous authors (Civan, 2010;Darabi et al, 2012;Florence et al, 2007;Fathi et al, 2012;Javadpour et al, 2007;Javadpour, 2009;Sakhaee-Pour and Bryant, 2012;Singh et al, 2014) have quantified these effects by modifying the slippage factor or determining the apparent permeability as a function of Knudsen number. Swami et al (2012) investigated and compared 10 theoretical and empirical models for quantifying Non-Darcy flow/Gas-Slippage effects in unconventional gas reservoirs; although these different approaches provided different results, they all indicated that the flow rate at nanoscale level is greater than that predicted from Darcy's equation.…”
Section: Introductionmentioning
confidence: 99%
“…Swami et al (2012) investigated and compared 10 theoretical and empirical models for quantifying Non-Darcy flow/Gas-Slippage effects in unconventional gas reservoirs; although these different approaches provided different results, they all indicated that the flow rate at nanoscale level is greater than that predicted from Darcy's equation. Specifically, compared to other theoretical models investigated in the study, the correlations proposed by Sakhaee-Pour and Bryant (2012) are considered to be most reliable because they are supported by well-designed laboratory experiment.…”
Section: Introductionmentioning
confidence: 99%